Synthesis of maleic and fumaric acids from furfural in the presence of betaine hydrochloride and hydrogen peroxide. Issue 1 (14th November 2016) - Araji, N.; Madjinza, D. D.; Chatel, G.; Moores, A.; Jérôme, F.; De Oliveira Vigier, K.
Abstract : Maleic acid (MA) and fumaric acid (FA) were produced from furfural with a total yield above 90% in the presence of an aqueous solution of betaine hydrochloride (BHC) and hydrogen peroxide. BHC can be recycled and can be used to convert xylose to MA and FA. Abstract : Here we report the successful valorisation of furfural into maleic acid (MA) and fumaric acid (FA) with a total yield above 90% using an aqueous solution of betaine hydrochloride (BHC) in the presence of hydrogen peroxide. BHC can be recycled for at least 4 cycles and it can be used to directly convert xylose to MA and FA.